Effects of in‐situ molecular oxygen exposure on the modulation of electrical properties of zinc oxide thin films grown by atomic layer deposition. Issue 2 (28th August 2014) - Park, Hui Kyung; Yang, Bong Seob; Kim, Myung Sang; Park, Sanghyun; Han, Jeong Hwan; Shin, Jae Cheol; Heo, Jaeyeong
<x xml:space="preserve">Abstract</x> The possibility of employing molecular oxygen (O2) for reducing the carrier concentration of zinc oxide (ZnO) thin films grown by atomic layer deposition was investigated. The exposure of O2 after the oxygen‐source pulse (deionised water) was eventually highly effective for decreasing the carrier concentration over 3–4 orders of magnitude. In contrast, the O2 pulse, when following the zinc source pulse (diethylzinc), had a minimal effect on the electrical property. Detailed structural, chemical and electrical analyses of the oxygen‐modulated ZnO thin films were conducted. Successful electrical modulation of the ZnO thin films was further demonstrated by fabricating back‐gated thin film transistors. The improvement in the on‐to‐off current ratio of the transistors was achieved by the proper exposure of O2.